Nutritional, Physicochemical, and Microbiological Quality of Soy Yoghurt Fortified with Fresh Moringa oleifera Leaf Aqueous Extract During Refrigerated Storage - Ita Fatkhur Romadhoni; Lilis Sulandari; Niken Purwidiani; Dwi Iriyani; Rita Ismawati; Kristian Triatmaja Raharja (Agro Bali : Agricultural Journal, 2026)
Growing interest in plant-based fermented foods has encouraged the development and evaluation of non-dairy yoghurt formulations. This study evaluated the effects of formulation and refrigerated storage time on the nutritional, physicochemical, and microbiological characteristics of soy yoghurt containing fresh Moringa oleifera leaf aqueous extract. Four formulations containing different combinations of moringa, garlic, and lime extracts were prepared in three independent production batches. Samples were stored at 4 ± 1 °C and analyzed on Days 7 and 14 for proximate composition, calculated energy value, pH, titratable acidity, aerobic plate count (APC), and lactic acid bacteria (LAB). Two-way analysis of variance showed significant formulation, storage time, and/or interaction effects on most measured variables, while titratable acidity was primarily affected by storage time. Formula B had the highest crude protein, fat, and calculated energy values at both sampling times, whereas Formula C had the highest carbohydrate content. Formula D showed the lowest APC on Day 7 and the highest LAB population at both sampling times, reaching 6.79 log₁₀ CFU/mL on Day 14. LAB populations remained above 6 log₁₀ CFU/mL in all formulations at both sampling times. These findings indicate that formulation composition influenced the measured characteristics of soy yoghurt between Days 7 and 14, although the independent contribution of fresh Moringa oleifera leaf aqueous extract could not be separated from those of garlic and lime.